2010
DOI: 10.1007/s10802-010-9443-9
|View full text |Cite
|
Sign up to set email alerts
|

The Delinquency Outcomes of Boys with ADHD with and Without Comorbidity

Abstract: This study examined the association between childhood ADHD and juvenile delinquency by examining data from the Pittsburgh ADHD Longitudinal Study (PALS), a follow-up study of individuals diagnosed with ADHD in childhood (ages 5-12) and recontacted in adolescence and young adulthood for yearly follow-up (age at first follow-up interview M= 17. 26, SD=3.17). Participants were 288 males with childhood ADHD and 209 demographically similar males without ADHD who were recruited into the follow-up study. Delinquency … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
114
0
1

Year Published

2012
2012
2018
2018

Publication Types

Select...
5
4

Relationship

0
9

Authors

Journals

citations
Cited by 140 publications
(119 citation statements)
references
References 57 publications
4
114
0
1
Order By: Relevance
“…Impulsivity appears to be the best predictor for the presence of CD among ADHD adolescents, with minor contributions from sensation seeking and other ADHD symptoms (67). ADHD and CD constitute a relevant association as it has been related with poor social functioning and the highest risk for delinquency outcomes (26,58,79,(82)(83)(84). In service sectors (which include the juvenile justice system), the public costs for adolescents with the ADHD-CD phenotype have been estimated to double the costs of those with ADHD alone (85).…”
Section: Adhd As a Risk Factor For Criminalitymentioning
confidence: 99%
See 1 more Smart Citation
“…Impulsivity appears to be the best predictor for the presence of CD among ADHD adolescents, with minor contributions from sensation seeking and other ADHD symptoms (67). ADHD and CD constitute a relevant association as it has been related with poor social functioning and the highest risk for delinquency outcomes (26,58,79,(82)(83)(84). In service sectors (which include the juvenile justice system), the public costs for adolescents with the ADHD-CD phenotype have been estimated to double the costs of those with ADHD alone (85).…”
Section: Adhd As a Risk Factor For Criminalitymentioning
confidence: 99%
“…It has also been proposed that ADHD, in the absence of a comorbid CD, is not associated with higher rates of either criminal behavior (22,23,(86)(87)(88)(89) or recidivism (90,91). However, several studies have reported that ADHD, when controlling for early aggressive behavior, ODD, CD, antisocial personality disorder, or other psychiatric comorbidities, is still a potential risk factor for delinquency and criminal offences (24,48,71,84,(92)(93)(94). Gudjonsson et al (25) recently estimated that ADHD contribution to the variance in nonviolent and violent delinquency among 11,388 young (16-24 years old) students was 8.2% and 8.8%, respectively, but these effects were almost completely mediated by the presence of peer delinquency and comorbidities, particularly CD and SUD.…”
Section: Adhd As a Risk Factor For Criminalitymentioning
confidence: 99%
“…26,27 In the context of this research and applying the model proposed in the current paper, people with ADHD can firstly be considered to be experiencing ill health in that they have areas of poor adaptive functioning, commonly expressed as impairments in academic performance and social relationships, 22,28 and later antisocial and delinquent behaviour. 29 This ill health can be considered to result from a lack of homeostasis at various points in the system, as illustrated by the work of Wåhlstedt et al 25 In this context problems with capacity can be viewed as the range of neuropsychological and cognitive impairments demonstrated by children and adults with ADHD both through standardised neuropsychological testing and through measures of academic achievement at school. 30 These impairments in capacity are likely to interfere with efficient energy transfer, as limited capacity in areas such as cognitive attention, executive functioning, 31 and specifically poor behavioural and response inhibition 32 are expressed as fidgeting, inattention, distraction, shouting out and other behaviours that are seen as disruptive in classroom and other settings.…”
Section: Applying the Model In Practice: Adhdmentioning
confidence: 99%
“…11 Comorbid disorders affect the psychosocial functioning of children with ADHD and increase their risk of developing delinquent behaviours. 12 Three different subtypes of ADHD exist: the predominantly inattentive, hyperactive-impulsive, or combined. The combined subtype is most prevalent in clinical studies, but population-based studies noted that the inattentive subtype is more common.…”
mentioning
confidence: 99%